Unit Trust Fund's Initial Service Charge And Its Determinants - Hiau Abdullah, Nur Adiana; Wong , Woei Chyuan (Asian Academy of Management (AAM), 2006)
This paper examines the variables that might explain the initial service charge (ISC) imposed on unit-holders of Malaysian unit trust funds in the year 1999. By using 39 openend unit trust funds, customer service and board structure variables are found to have a significant effect in explaining the variations of ISC. Financial performance variables do not seem to have any influence on the level of ISC charged to the unit-holders. Our results also showed that funds which charged higher ISC do not necessarily provide higher returns to investors. Furthermore, there are unit trust funds that are having an initial service charge beyond the maximum 10% level required by the Securities Commissions or did not fulfil the independent directors requirement.